2018
DOI: 10.1186/s12913-018-3784-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV infection and uptake of HIV/AIDS services among fisherfolk in landing Islands of Lake Victoria, north western Tanzania

Abstract: BackgroundNew HIV infections in Tanzania have been decreasing, however some populations remain at higher risk. Despite of that, evidence on the magnitude of HIV infection and the associated factors and HIV/AIDS services uptake among fisherfolk in Tanzania are inadequately explored. This study therefore aimed at determining prevalence of HIV infection and utilization of HIV/AIDS services among fishfolk in selected Islands of Lake Victoria for evidence-based interventions.MethodsCross-sectional study determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
6
23
0
Order By: Relevance
“…This nding resonates with Kapesa et al (2018), who found a similar result -higher odds of being HIV infected among shing communities around Lake Victoria, northwestern Tanzania (three times higher) than among farming communities. Sexual HIV risk was also observed to be associated with lower levels of education, inconsistent use of the condom, and being older (12). Results from eight shing communities in Uganda also indicate higher sexual HIV risk among lower educated people, women, divorced or in multiple sexual relations, and users of alcohol or illicit drugs before sexual encounters (23,25).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…This nding resonates with Kapesa et al (2018), who found a similar result -higher odds of being HIV infected among shing communities around Lake Victoria, northwestern Tanzania (three times higher) than among farming communities. Sexual HIV risk was also observed to be associated with lower levels of education, inconsistent use of the condom, and being older (12). Results from eight shing communities in Uganda also indicate higher sexual HIV risk among lower educated people, women, divorced or in multiple sexual relations, and users of alcohol or illicit drugs before sexual encounters (23,25).…”
Section: Introductionsupporting
confidence: 81%
“…This is higher in shing communities than in agrarian or trading communities in Rakai Community Cohort Study (RCCS) (24). This nding resonates with Kapesa et al (2018), who found a similar result -higher odds of being HIV infected among shing communities around Lake Victoria, northwestern Tanzania (three times higher) than among farming communities. Sexual HIV risk was also observed to be associated with lower levels of education, inconsistent use of the condom, and being older (12).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…This finding resonates with Kapesa et al (2018), who found a similar result – higher odds of being HIV infected among fishing communities around Lake Victoria, northwestern Tanzania (three times higher) than among farming communities. Sexual HIV risk was also observed to be associated with lower levels of education, inconsistent use of the condom, and being older [ 12 ]. Results from eight fishing communities in Uganda also indicate higher sexual HIV risk among lower educated people, women, divorced or in multiple sexual relations, and users of alcohol or illicit drugs before sexual encounters [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these intervention programs, there is still a high risk of MTCT infections. The national rate of MTCT for HIV is 6-11% [ 29 , 30 ]. More than 160,000 children are infected with HIV in the country.…”
Section: Introductionmentioning
confidence: 99%